Human capital developments an interdisciplinary approach for individual, organization advancement and economic improvement - Akinyemi, Gbenga M.; Zainal Abiddin, Norhasni (Canadian Center of Science and Education, 2013)
Human Capital Development implies the acquisition of kno wledge and intellectual stock through the means of education, for expansion of productivity, efficiency, performance and output. Human Capital Development Theory is applicable at every level of human setting and human organization: individual level, family level, community level, organization level, national level and international level. Therefore the theories can be used in interdisciplinary approach-involving two or more academic disciplines. On account of the importance of Human Capital Development Theory, this article reviewed the theory of Human Capital Development and various models underpinning it; with the aim of highlighting the relevance of Human Capital Theory in Human Resource Development as well as the models of Human Capital Development. The summary of the implication of human capital development theory emphasizes the more, the vitality of it to economic improvement and advancement of individuals and organizations.